Dear Colleagues! - article Editorial (LLC "Endo Press", 2021)
Endodontics in conservative dentistry in Russia is one of the most progressively developing areas. More and more doctors are mastering modern technologies in dentistry and are engaged in scientific research. In 2010, in Athens, the Russian Endodontic Association joined the International Federation of Endodontic Associations (IFEA), and in 2011 in Italy (Rome) - the European Endodontic Society (ESE), and since then Russian specialists annually participate in all congresses, receiving and sharing with colleagues the latest achievements in the world of endodontics. There is now the world and its own experience of scientific and practical research in the Journal articles. On behalf of the Board of the Endodontic Section, I congratulate the "Endodontics Today" Journal, the editorial staff on the 20th anniversary.President of the StAR Endodontic SectionDoctor of Medical Sciences, Professor I.M. Rabinovich